Utilization and Evaluation of Ethics Consultation Services in Neonatal Intensive Care - Pia Göbert; Pia von Blanckenburg; Rolf F. Maier; Carola Seifart (MDPI AG, 2024)
Background: The opportunities of perinatal medicine have improved, but this has also been accompanied by increasing ethical challenges. Clinical ethics consultation services (CEC) could support medical teams facing these. However, nothing is currently known about the availability, utilization and evaluation of CEC in German neonatology units. Methods: This study was designed as a national, descriptive, mixed quantitative-qualitative questionnaire study. The head physicians of the pediatric departments and the heads (medical and nursing) of the corresponding neonatal intensive care units of the 213 German perinatal centers were asked to participate. Results: Ninety percent of the respondents (responding rate 24.4-38.0%) stated that CEC are established and available. However, utilization is rather low [rarely N = 40 (54.1%), never N = 12, (16.2%), occasionally N = 19 (25.7%)], although it was rated as very helpful. There was a significant correlation between utilization and perceived general usefulness (r = 0.224, p = 0.033) and support (r = 0.41, p < 0.001); whereas evaluations differed significantly between professional groups (t = −2.298, p = 0.23, Cohen's d = 0.42). Conclusions: The contradiction between the low utilization despite positive evaluations could be related to perceived hurdles. These and the different perceptions within the professional groups give rise to the consideration of whether alternative approaches, e.g., liaison services, would be preferable in neonatology.